Use of and attitudes toward complementary and alternative medicine among obstetricians in Israel. Issue 2 (7th March 2013) - Samuels, Noah; Zisk‐Rony, Rachel Y.; Many, Ariel; Ben‐Shitrit, Gadi; Erez, Offer; Mankuta, David; Rabinowitz, Ron; Lavie, Ofer; Shuval, Judith T.; Oberbaum, Menachem
Abstract: Objective: To examine attitudes toward and use of complementary and alternative medicine (CAM) by obstetricians during pregnancy and childbirth. Methods: Between 2010 and 2011, obstetricians from 7 medical centers (n = 170) in Israel completed questionnaires examining the use and recommendation of CAM treatments during pregnancy and childbirth. Attitudes were examined via the CAM Health Belief Questionnaire (CHBQ). Results: Over half of the participants (58.8%) reported using at least 1 CAM treatment, and nearly two‐thirds had recommended or would recommend CAM to pregnant patients. By contrast, use of CAM during childbirth was recommended by only 26% of respondents. The total CHBQ score was moderately high (mean ± SD, 40.4 ± 7.30; possible range, 7.0–70.0), indicating an overall positive attitude toward CAM. Female board‐certified specialists answered more favorably regarding attitudes toward CAM ( P = 0.004). The structural validity of the CHBQ was examined using varimax rotation factor analysis, which produced a 3‐factor solution explaining 63.1% of the variance. Conclusions: Most obstetricians exhibited positive attitudes toward CAM and recommended its use during pregnancy, but did not support CAM use during childbirth. This discrepancy might be partly due to the involvement of Israeli obstetricians in predominantly high‐risk cases of childbirth requiring intervention.